Sie sind auf Seite 1von 2

c 1 r

1

r

dr (r dϕ

d

dr

) = 0

r dϕ

dr

=

ϕ(r) =

R

´

0

C

r

1

dr =C 1

R

= K = const.

) = 0

r dϕ

1

r

dr (r dϕ

d

dr

dr

=

c 2

ϕ(r) =

´

r

C

r

2

dr = C 2

r

´

E ( r )d 3 r = ¸ E(r)eˆ r da = 0

V

4πr 2 E(r) = 0

∂V

dr

= E(r) ϕ(r) = K = const.

´

E ( r )d 3 r = ¸ E(r)eˆ r da = 4πQ

V

∂V

4πr 2 E(r) = 4πQ E(r) =

Q

r 2

dr

= E(r) ϕ(r) =

´

r

2 dr = Q

Q

r

r

ρ(r) = 0

1

r

dr (r dϕ

d

dr

) = 0

ϕ(r) =

´

r

C

r

2

dr = C 1

r

C 2 C 1

ρ(r) = ρ 0

1

r

dr (r dϕ

d

dr

) = 4πρ 0

1 2

dr

r

= 4π ρ 0 r 3 + c 2 r 2 dϕ

3

dr

c 1 = 4π ρ 0 R 3 + c 2 c 2 = c 1 + 4π ρ 0 R 3

3

3

c 2 r 2

ϕ(r) =

´ R ρ 0 ( R 3 r) + C 1 ]dr = 4π ρ 0 (

[ 4π

3

r

2

r

2

3

r

R

´

r

R

r

3

2 dr

R

´

r

rdr) +

R

´

r

C

r

1

2

dr = 4π ρ 0 ( R 3

3

r

R 2 ) 2π (R 2 r 2 ) c 1 (

3

1

R

1 r )

r (c 1 4π

1

3

ρ 0 R 3 )

c 1 = 4π ρ 0 R 3 = Q

3

ϕ(r) = C 1

= Q

r

r

ϕ(r) = 2π ρ 0 (R 2 r 2 )

3

´

E ( r )d 3 r = ¸ E(r)eˆ r da = 4πQ

V

∂V

4πr 2 E(r) = 4πQ E(r) =

Q

r 2

dr

= E(r) ϕ(r) =

´

r

2 dr = Q

Q

r

r

´

E ( r )d 3 r = ¸ E(r)eˆ r da = 4πQ Q = 4π ρ 0 r 3

3

V

∂V

4πr 2 E(r) = 4πQ E(r) = Q

r

2 4π

3

ρ 0 r

dr

= E(r) ϕ(r) =

R

´

r

4π

3

ρ 0 rdr = 2π ρ 0 (r 2 R 2 )

3

E ( r ) = grad(ϕ(r)) = Ae λr

(

(

(

r

r

r

2

2

2

+

+

+

x

r

3

y

r

3

z

r

3

)

)

)

= Ae λr (

´

E ( r )d 3 r = ¸ E(r)d a = 4πQ Q = 4π ρ(r)r 3

3

V

ρ( r ) =

∂V

3

8π 2 ´

E ( r )

1

r

3

d 3 r

V

´

E ( r )d 3 r = ¸ E(r)d a = 4πQ

V

Q =

1

4π ´

V

∂V

E ( r )d 3 r

λ

2 +

r

1

r

3

) r = Ae λr ( λ +

r

1

2 )eˆ r

r